PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL 5E UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Muh Nasir; A. Wahab Jufri; Muhlis - (Jurnal Penelitian Pendidikan IPA, 2015)
This study aims to develop of learning package 5E model and analyze the effect of its implementation on the differences in student’s critical thinking and arguing skills. Development process follows R & D model by Dick and Carey. Research design follows pretest-posttest nonequivalent control group design. The population of this study was tenth graders of SMA 1 Woha Bima. Total population is 350 students from ten class. The sample was selected by simple random sampling technique and 131 students (four class) is obtained. X1 and X2 class are taught using the 5E models, while the X5 and X9 class with EEK models. Expert judgement results meet the criteria for the development of a very good result with an average value of 3.37. The results of experimental studies showed that: there is a difference in students’ critical thinking in the experimental and control group (t = 3,501, p = 0,001).Keywords: 5E Model, Critical Thinking Skills